Síndrome metabólica e trabalho em turnos em equipe de enfermagem de um hospital infantil - Holanda, Narriane Chaves Pereira de (2017)
Background: A relevant portion of the economically active world population is involved in some kind of night work and there are a relationship between shift work and short sleep duration. A few studies have shown the association between short sleep duration and negative consequences to the cardiometabolic health of night workers. The aim of this study was to analyze the association between shiftwork, sleep duration with metabolic syndrome risk factors in nursing personnel of a public hospital. Methods: A crosssectional study, involving nursing personnel of a children´s public hospital in João Pessoa, Brazil, was conducted. Sixty workers filled out a survey with socio-demographic, sleep (Karolinska Sleep Questionnaire), physical activity (International Physical Activity Questionnaire), Karasek's Job Demands-Control, and nutrition data (16-Food Intake Questionnaire). Body measurements and blood pressure were taken and blood was collected for glycemia, total cholesterol and portions of low-density lipoprotein and highdensity lipoprotein, triglycerides and leptin. The sample was divided into three groups according to the work shift of the participants (only morning shift, mixed - morning and night shifts, ex-night shift). To do the statistical analyzes, tests of the difference of the average of quantitative variables were done (ANOVA and Kruskal Wallis) and tests of proportion (chi-square test and Fisher exact) of quantitative variables to compare the three groups. In all tests was considered p < 0,05 as significant. The program used was the STATA 12.0 (Stata corp, Texas, USA). The ethical questions involving people were respected. Results: The participants average age was 39.8 years old (SD=10.5 years old). The prevalence of the metabolic syndrome in the studied population was 32%, however, there was no significant differences among the groups. Also, there were no significant differences among the studied groups regarding to socio-demographic, physical activity, food patterns, health characteristics, and job demands-control categories. Nevertheless, the group of morning and night workers reported sleep less (p<0.01), and showed a higher sleep debt (p<0.01) than the other groups in workdays. In addition, the higher proportion of workers with hypertriglyceridemia (TG ¿ 200 mg/dl; p=0.03) and diastolic arterial hypertension (DAP ¿ 90 mmHg; p=0.01) was observed in the morning and night shift group. Conclusion: The prevalence of metabolic syndrome in the studied population was above the general population. Although no differences were observed among the groups, the one which includes night shift showed more sleep disturbances than the others, and higher prevalence of two out of three risk factors to the metabolic syndrome diagnosis. The relationship between MS and shift work should be investigated in the light of work activity.